Deconstruction of DNA Methylation Patterns During Myogenesis Reveals Specific Epigenetic Events in the Establishment of the Skeletal Muscle Lineage. (21st April 2015) - carrió, Elvira; Díez‐Villanueva, Anna; Lois, Sergi; Mallona, Izaskun; Cases, Ildefonso; Forn, Marta; Peinado, Miguel A.; Suelves, Mònica
Abstract The progressive restriction of differentiation potential from pluripotent embryonic stem cells (ESCs) to tissue‐specific stem cells involves widespread epigenetic reprogramming, including modulation of DNA methylation patterns. Skeletal muscle stem cells are required for the growth, maintenance, and regeneration of skeletal muscle. To investigate the contribution of DNA methylation to the establishment of the myogenic program, we analyzed ESCs, skeletal muscle stem cells in proliferating (myoblasts) and differentiating conditions (myotubes), and mature myofibers. About 1.000 differentially methylated regions were identified during muscle‐lineage determination and terminal differentiation, mainly located in gene bodies and intergenic regions. As a whole, myogenic stem cells showed a gain of DNA methylation, while muscle differentiation was accompanied by loss of DNA methylation in CpG‐poor regions. Notably, the hypomethylated regions in myogenic stem cells were neighbored by enhancer‐type chromatin, suggesting the involvement of DNA methylation in the regulation of cell‐type specific enhancers. Interestingly, we demonstrated the hypomethylation of the muscle cell‐identity Myf5 super‐enhancer only in muscle cells. Furthermore, we observed that upstream stimulatory factor 1 binding to Myf5 super‐enhancer occurs upon DNA demethylation in myogenic stem cells. Taken altogether, we characterized the unique DNA methylation signature of skeletal muscle stem cells and highlighted the importance of DNA methylation‐mediated regulation of cell identity Myf5 super‐enhancer during cellular differentiation. Stem Cells2015;33:2025–2036